2021
DOI: 10.1016/j.molcel.2021.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Transient non-specific DNA binding dominates the target search of bacterial DNA-binding proteins

Abstract: Summary Despite their diverse biochemical characteristics and functions, all DNA-binding proteins share the ability to accurately locate their target sites among the vast excess of non-target DNA. Toward identifying universal mechanisms of the target search, we used single-molecule tracking of 11 diverse DNA-binding proteins in living Escherichia coli . The mobility of these proteins during the target search was dictated by DNA interactions rather than by their molecular weigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
87
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 113 publications
(135 reference statements)
16
87
2
Order By: Relevance
“…This property can allow them to form stable higher-level protein complexes and limit the gene accessibility effectively while facilitating the disassembly of the complexes as the protein levels fall (Figure 3). This view is also consistent with long DNA-occupancy times of HU and H-NS proteins (99%), which can assemble into large protein clusters on a DNA [59].…”
Section: A Concentration-dependent Residence Times Of Naps Can Have Regulatory Effects On Transcriptionsupporting
confidence: 78%
“…This property can allow them to form stable higher-level protein complexes and limit the gene accessibility effectively while facilitating the disassembly of the complexes as the protein levels fall (Figure 3). This view is also consistent with long DNA-occupancy times of HU and H-NS proteins (99%), which can assemble into large protein clusters on a DNA [59].…”
Section: A Concentration-dependent Residence Times Of Naps Can Have Regulatory Effects On Transcriptionsupporting
confidence: 78%
“…We had a stable, bound fraction (diffusion coefficient ( D ) of D bound = 0.005 μm 2 /s, bound time >>> bleach time), along with a mobile fraction ( D mobile = 0.5 μm 2 /s) (Figure 1D ). We chose a D mobile of 0.5 μm 2 /s, as it represents an appropriate lower limit for a diffusing molecule and is on the order of previously used values used in simulations to benchmark measurements of DBP ( 3 , 18 , 29 ). The value for D bound was selected for similar reasons.…”
Section: Resultsmentioning
confidence: 99%
“…We also characterized our approach across a range of different simulation conditions and compared it to the commonly-used MSD analysis approach for classifying states of molecules from SPT (Figure 3 ) ( 2 , 11 , 29 ). Here we tested the performance of our approach in conditions where we reduced the proportion of DNA-bound to diffusive molecules, the signal to noise ratio of the spots, and the diffusion coefficient of diffusive molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, LacI spends >90% of its time bound non-specifically, and visits the same binding site several times before binding to it, highlighting a potential trade-off between search speed and search accuracy [ 13 ]. Strikingly, it has been recently demonstrated that many other bacterial DNA binding proteins spend the majority of their time bound to non-specific sites on DNA in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%